MENGEMBANGKAN PEMASARAN UKM KREATIF DI TANGERANG SELATAN MELALUI SOCIAL MEDIA MARKETING - Khusnaini, Khusnaini; Wibowo, Oke (LPPM Universitas Pamulang, 2020)
The contribution of creative SMEs to GDP has not been optimal, only around 7.44% in 2016 and 7.41% in 2018. One of the contributing factors is that SMEs are able to produce goods that are creative, good and quality but do not know how to market it, so sales are relatively low. The marketing development program is important so that the production, sales and welfare of creative SMEs increase and their impact on the GDP and the Indonesian economy becomes more significant. Therefore, community service in the form of technical guidance (BIMTEK) was conducted to educate creative SMEs about the use of social media marketing as their marketing strategy. The number of internet and social media users in Indonesia is quite large so that marketing strategies with social media marketing have the potential to significantly increase marketing. Community service is limited to creative SME actors from three sub-sectors, namely fashion, crafts, and culinary in South Tangerang Region. The aim of BIMTEK is to provide knowledge and awareness of the importance of marketing through social media, while also providing skills in how to market products through social media. The results of this community service received quite good evaluation results from the BIMTEK participants and from the observers (observers) consisting of BEKRAF (Creative Economy Agency) and the Heads of SME Communities in the South Tangerang Region.